Early developmental environment and Olympic success: analysis of an Australian sporting "hotspot". (Final report submitted to the IOC Olympic Studies Centre in the framework of the PhD Students Research Grant Programme 2015) - O'Neill, K. (University of Sydney, 2016)
Summary: This study aims to identify an Australian sporting "hotspot" and the reasons for its ability to produce a greater relative number of Summer Olympic representatives 1984-2012 per head of the population. The overall study adopted a mixed-methods approach, with the first stage identifying the "hotspot" using publicly available, biographical data on all known (n = 2160) Australian Summer Olympians 1984-2012. The "hotspot" was examined through utilising a case study methodology within the context of Bronfenbrenner`s (1979, 2005) `Ecological Systems Theory`. Both community and Olympian`s perceptions regarding why the "hotspot" occurred and the influence it has had on the athletic development of these Olympians was investigated. The results determined that a range of demographic, geographic, historical, social and fortuitous factors contributed to the creation of this "hotspot". Access to built and natural facilities, climate, family influence, schools, strong community clubs, opportunity to train and compete with older athletes, access to role models, high socioeconomic status and an endemic sports culture were amongst key contributing factors underlying the development of this "hotspot". Although many of these features appear to be unique to the "hotspot" area in Perth, Western Australia, some have potential to be transferred to other athlete development environments. Volltext: http://doc.rero.ch/record/259006/files/Kristy_O_Neill_final_report_2015_IOC_PhD_Students_Research_Grant_Programme.pdf